Sustaining extended enterprise performance: A value co-creation perspective - Maria Bobbink; Andreas Hartmann; Geert Dewulf (Journal of Organization Design, 2016)
The Extended Enterprise, an advanced form of supply-chain integration, focusses on maximizing overall performance while also optimizing the performance of the stand-alone organizations involved. This necessitates not only inter-organizational collaboration but also inter-organizational performance measures. However, the continued use of and emphasis on, intra-organizational performance measures impedes collaborative efforts that transcend organizational boundaries and interests. We argue that an Extended Enterprise can only emerge and sustain through the development of a Service Logic perspective on value co-creation. Value co-creation encourages the establishment of performance measures for the evolving collaboration by taking into account the changing value-in-use of the products and services provided by all the firms involved. Our theoretical argument sheds new light on the formation of inter-organizational collaborations and addresses the role of organization design in this process.
Keywords: 650; Extended enterprise; Service logic; Value co-creation; Sense-making; Formalization; Meaning-giving; Co-created flexible performance measures